Obesity Is the Most Common Risk Factor for Chronic Liver Disease: Results From a Risk Stratification Pathway Using Transient Elastography. (November 2019) - Harris, Rebecca; Card, Timothy R.; Delahooke, Toby; Aithal, Guruprasad P.; Guha, Indra N.
Abstract : INTRODUCTION: Obesity has been associated with liver fibrosis, yet guidelines do not emphasize it as an independent risk factor in which to have a high index of suspicion of advanced disease. We aimed to elucidate the effect of a raised body mass index on the risk of liver disease using data from a community risk stratification pathway. METHODS: We prospectively recruited patients from a primary care practice with hazardous alcohol use and/or type 2 diabetes and/or obesity. Subjects were invited for a transient elastography reading. A threshold of ≥8.0 kPa defined an elevated reading consistent with clinically significant liver disease. RESULTS: Five hundred seventy-six patients participated in the pathway; of which, 533 patients had a reliable reading and 66 (12.4%) had an elevated reading. Thirty-one percent of patients with an elevated reading had obesity as their only risk factor. The proportion of patients with an elevated reading was similar among those with obesity (8.9%) to patients with more recognized solitary risk factors (type 2 diabetes 10.8%; hazardous alcohol use 4.8%). Obesity in combination with other risk factors further increased the proportion of patients with an elevated reading. In multivariate logistic regression, increasing body mass index and type 2 diabetes were significantly associated with an elevated reading. DISCUSSION: Obesity as a single or additive risk factor for chronic liver disease is significant. Future case-finding strategies using a risk factor approach should incorporate obesity within proposed algorithms.